Countering the demand for, and supply of, illicit tobacco: an assessment of the ‘North of England Tackling Illicit Tobacco for Better Health’ Programme - McNeill, Ann; Iringe-Koko, Belinda; Bains, Manpreet; Bauld, Linda; Siggens, Geoffrey; Russell, Andrew (BMJ Publishing Group, 2014)
Background Illicit tobacco (IT) undermines the effectiveness of tobacco control strategies. We assessed the implementation and impact of a new programme designed to reduce demand for, as well as supply of, IT, in the North of England, where IT was prevalent.